Sustainable development goals and quality of life targets: Insights from Metro Manila. (March 2015) - Porio, Emma
This article examines three frameworks utilized in assessing quality of life (QOL) and sustainability, namely, (1) the Millennium Development Goals (MDGs), (2) the United Nations Commission for Sustainable Development (UNCSD) framework for sustainable development, and the (3) Livable Cities Indicators (LCIs). The study assesses the efficiency, relevance/appropriateness, and effectiveness of these frameworks in assessing the quality of urban life in cities, with special reference to Metro Manila. What do these indicators really tell us about urban quality of life and whose quality of life is reflected or measured in these indicators? The article suggests that the understanding and assessment of the quality of life in cities can become broader and more relevant if we take into consideration that macro indicators may not reflect the socio-economic realities of different sub-groups, especially the politically and economically marginalized urban groups and classes. In short, these QOL frameworks and indicators are not sensitive to issues of social exclusion, inequality, and resource distribution among sub-groups, which have a great bearing on quality of life and sustainability, both in the cities of the North and the global South. To advance this goal, there is a need to contextualize, localize, and decentralize the production and utilization of the QOL knowledge systems.